Overhead labour costs in a neo-Kaleckian growth model with autonomous expenditures - Won Jun Nah; Marc Lavoie (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2018)
One of the most notable features of income distribution is the widening wage differential among workers: there is a redistribution in favor of top management at the detriment of ordinary workers. The paper incorporates this distinction between overhead managerial labour and direct labour into a neo-Kaleckian growth model with target-return pricing, where an autonomously growing demand component ultimately determines the long-run path of an economy. Our aim is to explore the role of overhead labour costs in the coevolution of income distribution and economic growth. When overhead labour is taken into account, the share of profits becomes an increasing function of the rate of utilization of capacity. This implies that empirical research based on the post-Kaleckian specification of the investment function may fail to isolate the pure profitability effects and is likely to be biased in finding a profit-led regime. Our model features convergence to a fully-adjusted position in the long run. This is achieved by simultaneous path-dependent adjustments, both in the normal rate of utilization of capacity and in the growth rate of sales expected by firms. We examine the parametric conditions under which the model achieves a wage-led growth regime, in the restricted sense that both the average rates of accumulation and utilization decrease during the transitional dynamics arising from an upward adjustment of the normal rate of profit. Moreover, it is shown that a more equitable wage distribution between the "working rich" and the "working poor" will strengthen the wage-led nature of the economy.
Keywords: E11; E37; O41; 330; neo-Kaleckian; growth; overhead labour; autonomous expenditures; targetreturn pricing